Oxytocin administration in the basolateral and central nuclei of amygdala moderately suppresses food intake. Issue 6 (11th April 2018) - Klockars, Oscar A.; Klockars, Anica; Levine, Allen S.; Olszewski, Pawel K.
Abstract : Oxytocin (OT) at acting central nuclei decreases meal size and reduces intake of palatable sweet solutions. It remains largely unclear as to which brain sites mediate OT's effect on palatability versus energy or the combination of those aspects of consumption. Here, we expanded the search for sites that mediate anorexigenic properties of OT by focusing on two subdivisions of the amygdala, its central (CNA) and basolateral (BLA) nuclei. We injected OT directly into the BLA or CNA in rats and assessed intake of standard chow induced by energy deprivation and intake of sweet solutions in nondeprived animals. We examined whether these effects are reversible by OT receptor (OTr) antagonism and whether OT presence in BLA or CNA induces taste aversion. We also determined the effect of energy deprivation and exposure to sweet saccharin on BLA and CNA expression of OTr mRNA. OT administration in BLA at 0.3 μg and in CNA at 1 μg reduced standard chow intake after deprivation by ~25%. Only administration of OT in BLA was effective in suppressing consumption of sucrose and saccharin solutions. The anorexigenic effects of OT in BLA and CNA were attenuated by OTr antagonist, L-368, 899, pretreatment. OT at anorexigenic doses did not promote acquisition of taste aversion. BLA OTr mRNA expression was affected by exposure to palatable saccharin, whereas that of CNA OTr, by energy deprivation. OT in the amygdala moderately decreases food intake. The functional relationship between amygdalar OT and energy intake versus palatability-driven intake depends on the discrete localization of the OTr within this complex structure.